Pesticides and pharmaceuticals data collected during two consecutive years in a Mediterranean micro-estuary - Tom Topaz; Julius Ben-Ari; Evgenia Kertsnus Banchik; Or Bassa; Roey Egozi; Yair Suari; Tal Sade; Hadar Zedaka; Merav Gilboa; Gitai Yahel; Benny Chefetz (PANGAEA, 2023)
The Alexander micro-estuary, located at the eastern edge of the Mediterranean Sea, is a typical example of small water bodies that suffer from a combination of urban and agricultural pollution, and overuse of its natural water sources. It is6.5 km long, with maximum depth of 3 m and maximum width of 45 m. To evaluate the anthropogenic stress on the system and its ability to mitigate pollution, water samples were collected within the framework of Ruppin extquotesingles Estuarine and Coastal Observatory (RECO, see Suari, Y. et al. 2019). Water samples were collected from the estuary head, which drains about 510 km2, and at a point 300 m upstream from the estuary mouth before water flows into the Mediterranean Sea. A total of 236 stormwater and 44 base-flow water samples between December 2016 and December 2018. Stormwater samples were collected every 0.25 – 4 h along the entire course of the flow events using an automated samplers (Sigma 900, Hach Company, Loveland CO, USA; and ISCO 3700 Full-Size Portable Sampler, Teledyne, Lincoln, NE, USA). Base-flow samples were taken once a month using a horizontal grab sampler (5 L, model 110B, OceanTest Equipment, Fort Lauderdale, FL, USA). All samples were filtered using 90mmGF/F filters (nominal pore size of 0.7 μm, MGF, Sartorius, Göttingen, Germany) and immediately frozen (-20 °C) before chemical analysis. Chemical analysis was performed using liquid chromatography with high-resolution mass spectrometry (LC–HRMS) analysis using a QExactive Plus hybrid FT mass spectrometer coupled with a Dionex Ultimate 3000 RS UPLC (Thermo Fisher Scientific, Waltham, MA, USA). The targeted analysis, which included 15 fungicides, 25 herbicides, 18 Insecticides, and 19 pharmaceuticals, concluded with a total of 21,142 entries. The dataset contains the sampling locations, sampling dates, flood section duration, discharge rate, and the total water volume discharged during the relevant period. The provided data offers an opportunity to explore the sources, transport, and impact of a large mixture of organic pollutants in a confined aquatic system located in an urbanized coastal environment.